Negotiating Religious Moderation in Pontianak City: Formal Constraints and Everyday Coexistence - Lubis, Putri Handayani; Puspitasari, Maria; Zurayah, Helva; Rachimoellah, Muhammad (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
This study examines how religious moderation is implemented and experienced in Pontianak City, with particular attention to the tension between formal institutional arrangements and everyday social interaction. Using a qualitative case study approach, the research draws on semi-structured in-depth interviews with 24 informants from religious-bureaucratic, educational-academic, and civil society backgrounds, complemented by non-participant observation in informal public spaces. The findings show three recurring patterns. First, formal regulatory mechanisms, particularly in the establishment of houses of worship, may impose uneven procedural burdens on minority groups. Second, inclusive educational initiatives may encounter social suspicion and limited institutional support, making moderation difficult to sustain in practice. Third, informal public spaces such as warung kopi provide more ordinary and flexible opportunities for interaction across religious and social boundaries, thereby supporting practical coexistence in everyday life. These findings suggest that religious moderation should not be understood only through policy discourse and formal programs, but also through the uneven ways it is negotiated and practiced in daily social settings. The study argues that strengthening religious moderation requires not only institutional design, but also wider community engagement and greater attention to informal spaces of coexistence in plural urban contexts.